2011
DOI: 10.1039/c1dt10084j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures, cellular uptake and apoptosis-inducing properties of highly cytotoxic ruthenium-Norharman complexes

Abstract: Three novel Ru(II) complexes of the general formula [Ru(N-N)(2)(Norharman)(2)](SO(3)CF(3))(2), where N-N = 2,2'-bipyridine (bpy, 1), 1,10-phenanthroline (phen, 2), 4,7-diphenyl-1,10-phenanthroline (DIP, 3) and Norharman (9H-pyrido[3,4-b]indole) is a naturally occurring β-carboline alkaloid, have been synthesized and characterized. The molecular structures of 1 and 2 have been determined by X-ray diffraction analysis. The cellular uptake efficiencies, in vitro cytotoxicities and apoptosis-inducing properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 83 publications
(27 reference statements)
3
74
0
Order By: Relevance
“…Both complexes showed an overal cellular uptake 10-100 times lower than for other ruthenium complexes. 44,88,89 Remarkably, 2 and particularly 1 still exhibited moderate to high toxicity upon light irradiation. Improving the cellular uptake of these compounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both complexes showed an overal cellular uptake 10-100 times lower than for other ruthenium complexes. 44,88,89 Remarkably, 2 and particularly 1 still exhibited moderate to high toxicity upon light irradiation. Improving the cellular uptake of these compounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…high phototoxicity, it has to be acknowledged that their cellular uptake into HeLa cells is quite moderate compared to other Ru(II) complexes. 44,88,89 To obtain more detailed information about the localization of 1and 2their subcellular accumulation was investigated. Briefly, HeLa cells were incubated with 1 and 2 for 4 h and subsequently the nuclei and mitochondria of the cells were isolated while the remaining cell material was kept as a residual fraction.…”
Section: Compoundmentioning
confidence: 99%
“…Among them, the apoptotic cell death through the activation of the mitochondrial dysfunctional pathway started to arise as a main cause of cytotoxicity exerted by Ru(II) polypyridyl complexes. [115][116][117][118][119] In 2010, combinatorial coordination chemistry followed by cytotoxicity screening allowed the discovery of a new antiproliferative complex ([Ru(tBu 2 bpy) 2 (phox)]PF 6 (46, Figure 10). 117 After a brief structureactivity relationship, Meggers and co-workers demonstrated that complex 46 showed the highest cytotoxicity when compared with the other tris-heteroleptic complexes tested.…”
Section: Mechanisms Of Action Involving Direct Interactions With Dnamentioning
confidence: 99%
“…Norharman is a naturally occurring β-carboline alkaloid. 119 The in vitro cytotoxicity of these complexes was evaluated against three cancer cell lines HepG2, HeLa, MCF-7 using cisplatin as a control.…”
Section: Mechanisms Of Action Involving Direct Interactions With Dnamentioning
confidence: 99%
“…[6] Deck monitoring unitfor underwater transmitter control signal can be transmitted via the signal cable, easy to view and change the transmitter's operating status. Transmitter through a low-voltage control signal to control the high voltage inverter switches off the inverse of the DC will be added to the transmitter sent out into the desired AC waveform, the inverter AC signal waveform frequency from the deck monitoring unit issued instructions to control.…”
Section: The Methods Of Mcsemmentioning
confidence: 99%